2021
DOI: 10.1021/acsaem.0c02615
|View full text |Cite
|
Sign up to set email alerts
|

Active and Stable Oxygen Reduction Catalysts Prepared by Electrodeposition of Platinum on Mo2C at Low Overpotential

Abstract: Decreasing the cost and improving the durability of polymer electrolyte membrane fuel cell (PEMFC) electrodes are two major unresolved challenges. Electrodeposition of low-dimensional Pt on transition metal carbide supports could be a way to simultaneously address both issues. Synthesis of low-dimensional Pt typically requires expensive equipment or techniques that are difficult to reproduce or scale. An electrodeposition-based technique to accomplish this goal is therefore highly desirable. The strong adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Featured with straightforwardness, power cost-effectiveness, and the short reaction period, electrodeposition has attracted much attention for the convenient synthesis of electrocatalysts. Encouraged by the aforementioned concerns, in this work, a Cu 2+ -guided electrodeposition strategy was proposed to synthesize a Cu and amorphous low-valence CoMo oxide nanocomposite (denoted as a-CoMoO 3 /Cu) from the CuCl 2 , CoCl 2 , NH 4 Cl, and (NH 4 ) 6 Mo 7 O 24 mixed solution. In this strategy, Cu 2+ is the crucial key for the formation of the a-CoMoO 3 /Cu nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…Featured with straightforwardness, power cost-effectiveness, and the short reaction period, electrodeposition has attracted much attention for the convenient synthesis of electrocatalysts. Encouraged by the aforementioned concerns, in this work, a Cu 2+ -guided electrodeposition strategy was proposed to synthesize a Cu and amorphous low-valence CoMo oxide nanocomposite (denoted as a-CoMoO 3 /Cu) from the CuCl 2 , CoCl 2 , NH 4 Cl, and (NH 4 ) 6 Mo 7 O 24 mixed solution. In this strategy, Cu 2+ is the crucial key for the formation of the a-CoMoO 3 /Cu nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they found that the catalyst prepared in the low-overpotential region exhibited the best stability after the accelerated stress test (AST, 5000 cycles) among all the contrast samples. 98 In addition, Lee et al selected highly conductive two-dimensional titanium carbide (Ti 3 C 2 ) as the support for Pt because of the expected SMSI between Pt and Ti 3 C 2 . Pt nanoparticles (4 nm) were loaded on three different Ti 3 C 2 supports including multi-, few-, and mono-layered Ti 3 C 2 (Fig.…”
Section: Carbon-free Carriersmentioning
confidence: 99%
“…[15][16][17] When commercial Nafion ® type membranes are employed, adequate humidification of the polymer electrolyte membrane and total water management during operation are crucial for PEMFC performance. [18][19][20] The water produced as a by-product will be used internally to maintain the membrane's hydration and prevent external water's excessive use for humidification. 2,19 Therefore, a PEMFC must be held when the by-product doesn't evaporate more quickly than the product.…”
mentioning
confidence: 99%
“…[18][19][20] The water produced as a by-product will be used internally to maintain the membrane's hydration and prevent external water's excessive use for humidification. 2,19 Therefore, a PEMFC must be held when the by-product doesn't evaporate more quickly than the product. 4,20 PEMFCs must be operated at a temperature of less than 100 o C. Due to their low-temperature functioning and water requirement, pure hydrogen (with a low CO concentration) must be utilized in PEMFCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation